Process Evaluation and Improvement of Learning and Development, Case: Company X - Peiponen, Niko (My University, 2018)
This master’s thesis is made as commission for a French multinational consulting, technology, outsourcing and professional services corporation. The research is limited geographically to Finland, Sweden and Norway. Within the company’s two Strategic Business Units, Application Services and Cloud Infrastructure Services respectively, the research is limited to the learning and development function. Aim of the thesis is to research the current state of learning and development and to propose areas for process improvement and process alignment based on the findings. Currently L&D is handled differently between countries and between business units which causes shortages of communication, inefficiencies in processes and duplicate work. This underlying problem the thesis strives to solve. Theoretical part is divided to four major themes. Firstly, different forms of knowledge are introduced. Next, individual and organizational learning frameworks, processes and sub-processes are presented. The theoretical part then goes on to describe the phases of knowledge conversion, presenting practical examples. Finally, two frameworks are presented which attempt to bridge the gap between individual and organizational learning. The research follows a case-study design. Data gathering methods are based for the most part on qualitative, in-person semi-structured interviews. The empirical evidence suggests that mutually things are moving towards a better direction, although common challenges include a lack of end-to-end system support, ambiguous and frequently changing focus areas for learning and development, and a lack of communication and visibility between countries and SBU’s. The improvement proposals relate to these challenges. Major areas for Nordic alignment proposed are unified data gathering, aligning calendar dates and implementing a unified certification process.
Keywords: Learning and Development; Process improvement; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|